Needs Analysis of English for Fine Arts Study Program Students as a Basis to Design English Teaching Materials - Sri Sukarni; Imansyah Imansyah (Muhammadiyah University of Mataram, 2022)
This research aimed to find out English teaching materials need of Fine Art study program students in learning English. The quantitative method was conducted in this research. In collecting the data, the researchers applied questionnaires for the students as the instrument of the research. There were 16 students of Fine Arts study program in the 2021-2022 academic year as the participants in this research. The results of this research revealed that in learning English students of Fine Arts study program need all language skills and the mostly needed language skill is speaking. They need speaking because will support their future career as artisan art working in English. Regarding language components, mainly required by the students is vocabulary. In addition, teaching materials related to fine arts are needed by the students, as well the teaching materials are taken from internet. Furthermore, pertaining to the objective of learning English that is to be able to communicate in English, the students need discussion before beginning to learn English course. This method can support students’ need in speaking skill. These students’ needs can be used as the basis to design English teaching materials..